(untitled) (The Review of Diabetic Studies, 2025)
The article examines the phenomena of corporate citizenship behavior from the time the idea first emerged in the literature to the present, as well as its definition and evolving characteristics. The relationship between organizational citizenship behavior (OCB) and concepts like courtesy, altruism, conscientiousness, civic virtue, and sportsmanship is also examined, as is how it relates to organizational culture, attitudes, and values. This analysis of the factors influencing OCB in the Chennai IT industry will help organizations focus on increasing employee productivity and, as a result, their overall performance. The purpose of the study is to investigate the connection between the aforementioned five parameters and OCB in the IT Sector. The information had been collected using a standardized questionnaire. 100 people made up the sample, and it was drawn using stratified random sampling. The result of this study is measures positively influence the employee’s organizational citizenship behaviour.